2021
DOI: 10.3389/fonc.2021.641053
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognostic Prediction in Pseudomyxoma Peritonei Originating From Mucinous Ovarian Cancer

Abstract: ObjectiveTo describe the clinicopathological characteristics of mucinous ovarian cancer (MOC)-derived pseudomyxoma peritonei (PMP) and identify prognostic factors for survival.MethodsMedical records from patients with MOC-derived PMP who attended the Aerospace Center Hospital, Beijing, China between January 2009, and December 2019 were retrospectively reviewed. Survival analysis was performed with the Kaplan-Meier method, the log-rank test, and a Cox proportional hazards model.ResultsCytoreductive surgery (CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Patients with low-grade mucinous cancers and those with lower peritoneal cancer index scores had improved overall survival. Notably, median overall survival times were shorter than 40 months for the entire cohort of patients with pseudomyxoma peritonei due to mucinous ovarian cancer in this study 56…”
Section: Systemic Treatmentmentioning
confidence: 59%
See 1 more Smart Citation
“…Patients with low-grade mucinous cancers and those with lower peritoneal cancer index scores had improved overall survival. Notably, median overall survival times were shorter than 40 months for the entire cohort of patients with pseudomyxoma peritonei due to mucinous ovarian cancer in this study 56…”
Section: Systemic Treatmentmentioning
confidence: 59%
“…51 A group from China published their experience with patients diagnosed with pseudomyxoma peritonei secondary to mucinous ovarian cancer. 56 Over a 10-year period they performed cytoreduction and HIPEC in 22 patients. Similar to van Driel et al, this group used cisplatin for perfusion.…”
Section: Systemic Treatment Primary Treatmentmentioning
confidence: 99%
“…We scored the prior surgical outcomes with PSS for each patient; PSS-0 was the rating for no surgery or biopsy, PSS-1 for surgery in one abdominal region only, PSS-2 for surgery in two to five regions, and PSS-3 for surgery in more than five regions 5 . A recent report showed that the univariate analysis of poor prognosis in patients with peritoneal pseudomyxoma after neoplasm reduction included women (P = 0.0127), intestinal obstruction before treatment (P = 0.00791) and PSS (P = 0.0054).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained cutoff values based on objective data for gender, intestinal obstruction, weight loss, PSS, RBC, Hb, ALB, right hemicolectomy and HIPEC, among which the cutoff values for Hb and ALB were based on the lower limit of the normal reference range. The cutoff values of age, PCI, and CCR were obtained according to the previous grouping of our research center [5][6][7][8] . Due to the wide range of hospitalization days, we selected one month as the cutoff value.…”
mentioning
confidence: 99%
“…Oncological adequacy of surgery requires monoblock removal of the tumor-affected organ and resection of the blood vessel, followed by its reconstruction [7]. It should be recognized that the performance of operations related to resection, as well as one or another type of vascular plasticity in pelvic extraorgan tumors, can only afford large, technically equipped surgical centers with qualified surgical personnel [6].…”
Section: загальна та невідкла дна хірургіяmentioning
confidence: 99%